FBXW7 attenuates tumor drug resistance and enhances the efficacy of immunotherapy - Chen, Shimin; Lin, Jichun; Zhao, Jiaojiao; Lin, Qian; Liu, Jia; Wang, Qiang; Mui, Ryan; Ma, Leina (Frontiers in Oncology, 2023)
FBXW7 (F-box and WD repeat domain containing 7) is a critical subunit of the Skp1-Cullin1-F-box protein (SCF), acting as an E3 ubiquitin ligase by ubiquitinating targeted protein. Through degradation of its substrates, FBXW7 plays a pivotal role in drug resistance in tumor cells and shows the potential to rescue the sensitivity of cancer cells to drug treatment. This explains why patients with higher FBXW7 levels exhibit higher survival times and more favorable prognosis. Furthermore, FBXW7 has been demonstrated to enhance the efficacy of immunotherapy by targeting the degradation of specific proteins, as compared to the inactivated form of FBXW7. Additionally, other F-box proteins have also shown the ability to conquer drug resistance in certain cancers. Overall, this review aims to explore the function of FBXW7 and its specific effects on drug resistance in cancer cells.